Designing an Information System for Aspirations and Complaints in Semambung Village, Wonoayu District - Muhammad Afif Fahrurozi; Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
The Wonoayu Subdistrict Government continues to make efforts to improve the quality of community services, one of which is by including community participation through community aspirations and complaints. The information system for the service of aspirations and community complaints at the village office of Semambung Village, Wonoayu District, is a system that serves the aspirations and complaints of the community related to the performance, services, facilities and infrastructure of the community of Semambung Village, Wonoayu District. The system is built using PHP programming language by using Codeigniter and Mysql frameworks as Database Storage. The final result of this study is an information system for the service of aspirations and complaints of Semambung Village, Wonoayu District, where in this system the community can fill out directly the aspiration and complaint input form and can see news about the development of Semambung Village, Wonoayu District, Sidoarjo Regency.